2020
DOI: 10.1152/ajpheart.00521.2019
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in electrophysiology and calcium handling: implications for pediatric cardiac research

Abstract: Rodent models are frequently employed in cardiovascular research, yet our understanding of pediatric cardiac physiology has largely been deduced from more simplified two-dimensional cell studies. Previous studies have shown that postnatal development includes an alteration in the expression of genes and proteins involved in cell coupling, ion channels, and intracellular calcium handling. Accordingly, we hypothesized that postnatal cell maturation is likely to lead to dynamic alterations in whole heart electrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 66 publications
(94 reference statements)
2
19
0
Order By: Relevance
“…Awake measurements indicated that P8 hypoxic animals had a slightly longer P-wave duration (13.9 ± 0.5 vs. 12.4 ± 0.3 ms, q = 0.09) and PR interval (46.9 ± 2 vs. 37.3 ± 0.9 ms, q < 0.01). Heart rate variability was also decreased in hypoxic animals (RMSSD: 3.9 ± 0.5 vs. 7.1 ± 1.4, q < 0.005), a parameter that normally increases with postnatal development (29). In vivo ECG parameters were also altered under isoflurane sedation (Fig.…”
Section: Hypoxia Caused Bradycardia and Slowed Conduction At P8mentioning
confidence: 84%
See 2 more Smart Citations
“…Awake measurements indicated that P8 hypoxic animals had a slightly longer P-wave duration (13.9 ± 0.5 vs. 12.4 ± 0.3 ms, q = 0.09) and PR interval (46.9 ± 2 vs. 37.3 ± 0.9 ms, q < 0.01). Heart rate variability was also decreased in hypoxic animals (RMSSD: 3.9 ± 0.5 vs. 7.1 ± 1.4, q < 0.005), a parameter that normally increases with postnatal development (29). In vivo ECG parameters were also altered under isoflurane sedation (Fig.…”
Section: Hypoxia Caused Bradycardia and Slowed Conduction At P8mentioning
confidence: 84%
“…ECG segments were quantified using ecgAuto software (emka Technologies) for heart rate, heart rate variability, atrial depolarization time (Pwave duration), atrioventricular (AV) conduction time (PR interval), ventricular depolarization time (QRS duration), and ventricular repolarization time [QT interval; uncorrected as heart rate does not significantly alter QT interval in mice (28)]. Heart rate variability was measured as a root mean square of the successive differences (RMSSD) (28,29). Due to motion artifact, only clearly discernable ECG parameters were included in the analysis for each animal.…”
Section: In Vivo Electrocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, since its first use for optical mapping in 2007, blebbistatin has all but replaced the other available EC uncouplers. In fact, in the last three years alone, blebbistatin was used twice as often (1,29,36,41,51,56,59,69,74,76,78,83,85,87) as any other uncoupler for imaging applications (25,27,33,46,54,55,80). The use of BDM/DAM and CytoD for optical mapping has essentially ceased, yet due to its lower cost, BDM/DAM may still be a reasonable choice for larger animal (i.e., non-rodent) studies (10,23,25,35,52,70,77), which require larger amounts of an EC uncoupler (72).…”
Section: Excitation-contraction Uncouplingmentioning
confidence: 99%
“…In contrast, the development of optical mapping offered a new mapping approach with superior spatial resolution (53) that is determined by the image sensor specifications (sensor size, number of pixels, and quantum efficiency) and the optical field of view (9). Additionally, the use of calciumsensitive probes enabled simultaneous measurements of electrical activity and intracellular calcium cycling, as demonstrated by Choi and Salama at the turn of the century (15), and now provides unprecedented insight into ECC parameters in normal and diseased hearts (31,42,56,74,76,83).…”
Section: Introductionmentioning
confidence: 99%